Thermogenesis, vocalization, and temperature preference of 1-day-old chicken hatchlings after cold-exposure in late embryogenesis - Toro-Velasquez, Paula Andrea [UNESP]; Mortola, Jacopo P. (Springer, 2014)
In a thermal gradient the preferred ambient temperature (T (a) pref) of chicken hatchlings is a few degrees lower than thermoneutrality. To investigate whether a correlation may exist between T (a) pref and the autonomic thermogenic capacity or not we studied a group of hatchlings (N = 15) exposed to cold at end-incubation, a procedure known to increase their postnatal thermogenesis. Chicken embryos were exposed to cold (34.5 A degrees C instead of 38 A degrees C) at days 18-20 of incubation. By comparison to Controls (N = 15), they hatched a few hours later, with similar body weight, body temperature, vocalization (number of sounds produced per unit time), and oxygen consumption (, measured in a respirometer by an open-flow methodology). When exposed to slow cooling these hatchlings had a higher lower critical temperature (LCT) of thermoneutrality and higher , and slightly higher vocalization than Controls. In a thermal gradient, T (a) pref averaged 34.3 +/- A 0.3 A degrees C, or 1 A degrees C higher than in Controls (33.4 +/- A 0.3 A degrees C; P < 0.05), in proportion with their higher LCT (38 +/- A 0.1 A degrees C instead of 36.7 +/- A 0.3 A degrees C; P < 0.001), so that the T (a) pref - LCT difference (-3.6 +/- A 0.3 A degrees C) was similar to Controls (-3.3 +/- A 0.3 A degrees C). In conclusion, in chicken hatchlings T (a) pref was lower than LCT irrespective of the magnitude of their thermogenic response. It was estimated that, at T (a) pref, was similar to 20 % higher than at thermoneutrality. Such metabolic increase could carry some physiological advantage and the choice of T (a) pref may reflect the hatchling's needs to maintain slightly elevated.
Keywords: Bird; newborn; Behaviour; Thermoneutrality; Thermoregulation